Process method for preparing modified white carbon black from clay vanadium ore vanadium extraction acid leaching tailings
Through the non-grinding alkali-soluble silicon leaching process and in-situ grafting modification technology, the tailing reduction and particle size problems in clay vanadium ore vanadate leaching tailings treatment and white carbon black preparation were solved, and high-quality modification was prepared. white carbon black achieves efficient utilization of resources and improves performance.
Patent Information
- Application Number
- CN202411018819.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-29
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-07-29
AI Technical Summary
The treatment of vanadate leach tailings and preparation of white carbon black in clay vanadium ore has problems such as insufficient reduction of tailings, large particle size and poor performance. The traditional process is complex and costly, making it difficult to apply on a large scale on industrial scale.
The vanadate leach tailings of clay vanadium ore are mixed with sodium hydroxide and heated by non-grinding alkali-soluble silicon leaching process, and then the self-distribution electrolyte SC-1 and a new combination modifier are added for in-situ graft modification to form a high Massive modified white carbon black reduces tailings and improves the hydrophobicity and specific surface area of the product.
The tailings amount was effectively reduced by more than 85%, and modified white carbon black with small particle size, large specific surface area and strong hydrophobicity was prepared, which improved the application range and performance of the product and achieved efficient utilization of clay vanadium ore resources.
Smart Images

Figure CN119219003A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a process for preparing modified white carbon black from acid leaching tailings of vanadium extraction from clay vanadium ore, belonging to the technical field of treatment and utilization of industrial waste slag. Background Art
[0002] Clay vanadium ore is one of the important raw materials for vanadium extraction in my country. It is a clay mineral with low vanadium grade and silicon dioxide as the matrix (silicon dioxide content is about 80%). According to statistics, 150 to 200 tons of tailings will be produced for every ton of vanadium pentoxide produced. The tailings from vanadium acid leaching not only have a large amount of highly corrosive substances, but also contain a variety of heavy metal elements. If only traditional storage and landfill are used, it will not only occupy a large amount of land resources, but also may pollute water and soil resources. In recent years, the country has continuously increased the development and utilization of clay vanadium ore, and the amount of vanadium acid leaching tailings has also increased accordingly, and the pressure on the environment has also increased. It is urgent to explore its effective reduction and efficient resource treatment and disposal methods. Therefore, it is of great significance to efficiently extract silicon dioxide from clay vanadium ore vanadium acid leaching tailings and prepare modified white carbon black.
[0003] White carbon black, also known as hydrated silicon dioxide (SiO2·nH2O), has the characteristics of high temperature resistance, non-combustion, porosity, high surface activity and large specific surface area. It is widely used in rubber, plastic, ink, paper and pharmaceutical fields. The preparation methods of white carbon black include gas phase method, precipitation method, microemulsion method, sol-gel method and so on. The gas phase method and precipitation method are the two main methods in industrial production. Among them, the gas phase method for producing white carbon black has the limitations of complex process, high requirements for production equipment and high production cost, which makes the gas phase method unable to be used on a large scale in industry. Therefore, the precipitation method is generally used to produce white carbon black on a large scale. It should be pointed out that in the preparation of white carbon black by precipitation method, the type and amount of electrolyte is one of the key links, which needs further research and development. This is because: there are more silica gel particles in water glass, which are oxidized by a large amount of OH under alkaline conditions. - Surrounded by the solid particles, a stable charged body is formed, which is not easy to precipitate. After adding the electrolyte, the cations in the solution can weaken the electrostatic interaction between the particles, reduce the surface charge of the silica particles, and finally cause condensation, which is conducive to the precipitation method to produce white carbon black.
[0004] In addition, the surface of the silica obtained by the ordinary process contains a large number of active hydroxyl groups. The presence of these active hydroxyl groups will make the hydrophobicity of the silica product worse and the particle size larger. The active hydroxyl groups on the surface of silica will further increase the surface energy of silica, enhance the aggregation of silica and reduce the dispersibility of silica. Therefore, in order to further increase the application scope of silica, it is necessary to modify the surface of the silica product. At present, the modification method of silica products is mainly chemical. Chemical modification is mainly divided into silane coupling agent modification method, alcohol ester modification method, surfactant modification method, organic halogenated silane modification method, etc. Among them, the in-situ grafting modification of silica with a surfactant will not cause changes in the phase form and crystal structure of silica. After modification, many properties of silica can be greatly improved, which is a very promising method. In this method, surfactants (i.e., modifiers) are the top priority.
[0005] In order to achieve effective reduction and disposal of clay vanadium ore, efficient resource utilization, and prepare high-quality (smaller particle size, stronger hydrophobicity, larger specific surface area) white carbon black products, the present invention is specially proposed. Summary of the invention
[0006] In order to solve the problem of reducing the amount of tailings from vanadium extraction from clay vanadium ore and recycling them, and to solve the problems of low precipitation rate and large particle size of white carbon black products in the existing preparation of white carbon black, the present invention proposes a process for preparing modified white carbon black from tailings from vanadium extraction from clay vanadium ore, which specifically includes the following steps:
[0007] (1) Alkali leaching of silicon without grinding: The tailings from vanadium acid leaching of clay vanadium ore are mixed with sodium hydroxide and water in a certain ratio without grinding, and then heated for leaching reaction; after the reaction is completed, the tailings are cooled to below 50°C, and the filter residue and filtrate are obtained by solid-liquid separation, and the weight of the tailings is reduced by more than 85%, that is, the weight of the filter residue is within 15% of the weight of the tailings from vanadium acid leaching of clay vanadium ore, and the filtrate is water glass.
[0008] (2) Preparation and modification: Add the self-compounded electrolyte SC-1 to water glass, and add a new combination modifier for in-situ grafting modification, then add acid for neutralization, and age at a constant temperature to produce silica gel precipitation. The silica gel is dried and ground to obtain the modified silica product;
[0009] The self-compounded electrolyte SC-1 includes 60% to 80% by mass of sodium sulfate and 20% to 40% by mass of sodium carbonate;
[0010] The novel combined modifier comprises components with a mass distribution ratio of 40% to 80% of hexadecyltrimethylammonium bromide (CATB) and 20% to 60% of sodium dodecyl sulfate (SDS).
[0011] Preferably, the tailings in step (1) are from the acid leaching process of vanadium extraction from clay vanadium ore, and have a silicon dioxide content of more than 85% and a particle size of -2 mm to -4 mm. No acid leaching and impurity removal treatment is performed before alkali leaching of silicon, and no grinding treatment is performed.
[0012] Preferably, in step (1), the alkali-slag ratio, i.e., the mass ratio of sodium hydroxide to the tailings from vanadium acid leaching of clay vanadium ore, is 0.3-1; the liquid-solid ratio, i.e., the mass ratio of water to the tailings from vanadium acid leaching of clay vanadium ore, is 3-6; the heating temperature is 180-220° C.; the reaction time is 50-100 min; and air cooling is adopted to cool the mixture to below 50° C.
[0013] Preferably, the mass of the filter residue obtained by solid-liquid separation in step (1) is within 15% of the mass of the tailings from vanadium acid leaching of clay vanadium ore, that is, after non-abrasive alkali dissolution of silicon, the tailings from vanadium acid leaching of clay vanadium ore are reduced by more than 85%, which can effectively achieve the reduction treatment of the tailings from vanadium acid leaching of clay vanadium ore.
[0014] Preferably, the amount of the self-prepared electrolyte SC-1 added in step (2) is 2% to 6% of the mass of the tailings from vanadium acid leaching of clay vanadium ore.
[0015] Preferably, in step (2), the preparation and modification of white carbon black are carried out simultaneously, that is, a self-assembled and compounded new combination modifier is added for in-situ grafting modification, and the amount of the new combination modifier is 2% to 5% of the mass of the clay vanadium ore vanadium acid leaching tailings.
[0016] Preferably, in step (2), acid is added to neutralize the solution until the pH value is 7.0 to 8.5; and the constant temperature aging conditions are controlled at: 60 to 90° C., 60 to 120 min.
[0017] After adopting the above technical solution, the present invention has the following beneficial effects compared with the prior art:
[0018] (1) After vanadium extraction, clay vanadium ore will inevitably produce a large amount of high-silica acid leaching tailings. In recent years, the country's development and utilization of clay vanadium ore has been increasing, and the amount of vanadium acid leaching tailings has also increased accordingly, and the pressure on the environment has also become increasingly greater. It is urgent to explore its reduction and resource-based treatment and disposal methods. The present invention uses clay vanadium ore vanadium acid leaching tailings as raw materials, and leaches silicon through unground alkali dissolution, which not only reduces the amount of tailings by more than 85%, can effectively achieve the reduction of tailings, but also provides a cheap and easily available silicon source for the preparation of white carbon black, which can provide a new path for the comprehensive utilization of clay vanadium ore acid leaching tailings.
[0019] (2) During the acid leaching process of vanadium extraction from clay vanadium ore, most of the acid-soluble impurities have been dissolved and leached out, and the main component of the acid leaching tailings produced is silicon dioxide, with a content of more than 85%. There are very few other impurities that are harmful to the preparation of white carbon black. Therefore, the present invention does not require acid leaching and impurity removal treatment before alkali leaching of silicon, nor does it require grinding treatment.
[0020] (3) Water glass, i.e., the filtrate of the un-abrasive alkali dissolution process of silicon, has colloidal properties. According to the DLVO theory, the stability of colloidal solutions is related to whether the van der Waals force and the double layer pressure at the solid-liquid interface are balanced. Adding sufficient electrolytes to the solution can compress the double electron layer around the colloid particles and reduce the repulsive energy. At this time, the colloid particles are mainly attracted, the distance between the particles is reduced, and the colloid particles become unstable and precipitate. However, when the double layer can no longer be compressed, too many electrolyte ions will hinder the aggregation of the colloid particles. Adding inorganic salt electrolytes to water glass can increase the number of micro-colloidal ions in the water glass-electrolyte system and form a large number of sodium silicate polymers. The system polymer has a porous structure, and the SiO2 precipitate generated on this basis has a rich porous structure and a loose structure. In addition, a single electrolyte often has limited efficacy. By controlling the type and compound ratio of the electrolyte, it can play a positive synergistic role, and better results can be obtained while reducing the dosage. In view of this, in the present invention, the electrolyte SC-1 is independently compounded, including 60% to 80% by mass of sodium sulfate and 20% to 40% by mass of sodium carbonate; SC-1 can effectively promote water glass to form small agglomerates of SiO2, improve the precipitation rate, and then easily form loose and porous SiO2 precipitation, thereby obtaining a high-quality white carbon black product.
[0021] (4) If you want to further expand the application range of white carbon black, you must modify the surface of the white carbon black product. Using surfactants to graft white carbon black in situ will not cause changes in the phase form and crystal structure of white carbon black. After modification, many properties of white carbon black can be greatly improved. This is a very promising method. In this method, surfactants, i.e. modifiers, are of utmost importance.
[0022] Hexadecyltrimethylammonium bromide (CATB) is a cationic surfactant, and sodium dodecyl sulfate (SDS) is an anionic surfactant. Both can be covered on the surface of white carbon black by chemical adsorption to achieve graft modification. Similarly, a single surfactant often has limited efficacy, but by controlling the type and compounding ratio of the surfactant, it can play a positive synergistic role, and better effects can be obtained while reducing the dosage. In view of this, in the present invention, the modifier, i.e., the surfactant, is independently compounded and assembled, and the mass component ratio of the new combined modifier is: 40% to 80% hexadecyltrimethylammonium bromide (CATB), 20% to 60% sodium dodecyl sulfate (SDS). CATB and SDS can be positively synergistically adsorbed on the hydroxyl groups on the surface of white carbon black, improve its hydrophobic properties, and form a network structure on the surface of white carbon black, preventing the white carbon black particles from further agglomerating, reducing its particle size, forming a loose and porous structure, and enhancing its various performances.
[0023] Combining the above aspects, the process method of the present invention can turn the tailings of vanadium acid leaching from clay vanadium ore into treasure, realize its effective reduction treatment and efficient resource utilization. At the same time, all indicators of the prepared white carbon black product meet the requirements of industry standards. The modified white carbon black product has stronger hydrophobicity, larger specific surface area and smaller particle size, and the scope of application can be greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a process flow chart of the present invention.
[0025] Figure 2 This is a particle size analysis diagram of the white carbon black product prepared in Example 1.
[0026] Figure 3 This is a particle size analysis diagram of the white carbon black product prepared in Example 2.
[0027] Figure 4 This is a particle size analysis diagram of the white carbon black product prepared in Comparative Example 1.
[0028] Figure 5 This is a particle size analysis diagram of the white carbon black product prepared in Comparative Example 2.
[0029] Figure 6 This is a particle size analysis diagram of the white carbon black product prepared in Comparative Example 3.
[0030] Figure 7 This is a particle size analysis diagram of the white carbon black product prepared in Comparative Example 4. DETAILED DESCRIPTION
[0031] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. However, the following embodiments are merely simple examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.
[0032] Example 1
[0033] A process for preparing modified white carbon black from clay vanadium ore vanadium acid leaching tailings, which is specifically implemented as follows:
[0034] (1) Non-grinding alkali leaching silicon: The tailings of vanadium extraction from clay vanadium ore were taken from Shangluo, Shaanxi, with a particle size of -2mm and a silicon dioxide content of 86.8%. The tailings of vanadium extraction from clay vanadium ore were not ground or subjected to acid leaching and impurity removal treatment, but were directly mixed with sodium hydroxide and water for heating and leaching reaction: the alkali-slag ratio, i.e., the mass ratio of sodium hydroxide to the tailings of vanadium extraction from clay vanadium ore was 0.8; the liquid-solid ratio, i.e., the mass ratio of water to the tailings of vanadium extraction from clay vanadium ore was 5; the heating temperature was 200℃; the reaction time was 90min. After the reaction was completed, air cooling was used to cool to below 50℃ for solid-liquid separation to obtain filter residue and filtrate (water glass), of which the yield of filter residue was 10.4%, which means that 89.6% of the tailings of vanadium extraction from clay vanadium ore were reduced.
[0035] (2) Preparation and modification: Add a self-compounded electrolyte SC-1 to water glass, and add a new combination modifier for in-situ grafting modification, the amount of SC-1 is 3% of the mass of the tailings of vanadium acid leaching from clay vanadium ore, and the amount of the new combination modifier is 3% of the mass of the tailings of vanadium acid leaching from clay vanadium ore, then add acid to neutralize to pH 8, and age at a constant temperature of 80°C for 120 minutes to produce a silica gel precipitate, which is dried and ground into a modified white carbon black product; wherein the self-compounded electrolyte SC-1 includes 60% by mass of sodium sulfate and 40% by mass of sodium carbonate; the new combination modifier includes a mass component ratio of 40% hexadecyltrimethylammonium bromide (CATB) and 60% sodium dodecyl sulfate (SDS).
[0036] In this embodiment, the silicon dioxide leaching rate is as high as 98.64%, and the tailings of vanadium extraction from clay vanadium ore are reduced by nearly 90%. By adding the self-compounded electrolyte and the new combination modifier, the specific surface area of the modified white carbon black product is 316.62m 2 / g, median particle size (D 50 ) is only 3.86μm( Figure 2 As shown), SiO2 content reaches 99.3%, and the product quality meets the requirements of HG / T3061-2020 industry standard.
[0037] Example 2
[0038] A process for preparing modified white carbon black from clay vanadium ore vanadium acid leaching tailings, which is specifically implemented as follows:
[0039] (1) Non-grinding alkali leaching silicon: The tailings of vanadium extraction from clay vanadium ore were taken from Xichuan, Henan, with a particle size of -3mm and a silicon dioxide content of 85.7%. The tailings of vanadium extraction from clay vanadium ore were not ground or subjected to acid leaching and impurity removal treatment, but were directly mixed with sodium hydroxide and water for heating and leaching reaction: the alkali-slag ratio, that is, the mass ratio of sodium hydroxide to the tailings of vanadium extraction from clay vanadium ore, was 0.75; the liquid-solid ratio, that is, the mass ratio of water to the tailings of vanadium extraction from clay vanadium ore, was 3; the heating temperature was 180℃; the reaction time was 50min. After the reaction was completed, air cooling was used to cool to below 50℃ for solid-liquid separation to obtain filter residue and filtrate (water glass), of which the yield of filter residue was 12.3%, which means that 87.7% of the tailings of vanadium extraction from clay vanadium ore were reduced.
[0040] (2) Preparation and modification: Add a self-compounded electrolyte SC-1 to water glass, and add a new combination modifier for in-situ grafting modification, the amount of SC-1 is 3.5% of the mass of the tailings from the vanadium acid leaching of clay vanadium ore, and the amount of the new combination modifier is 3% of the mass of the tailings from the vanadium acid leaching of clay vanadium ore, then add acid to neutralize to pH 8.5, and age at a constant temperature of 60°C for 60 minutes to produce a silica gel precipitate, which is dried and ground into a modified silica product; wherein the self-compounded electrolyte SC-1 includes 80% by mass of sodium sulfate and 20% by mass of sodium carbonate; and the new combination modifier includes a mass component ratio of 80% hexadecyltrimethylammonium bromide (CATB) and 20% sodium dodecyl sulfate (SDS).
[0041] In this embodiment, the silicon dioxide leaching rate is as high as 97.2%, and the effective reduction of the tailings of vanadium extraction from clay vanadium ore acid leaching is 87.7%; by adding the self-compounded electrolyte and the new combined modifier, the specific surface area of the modified white carbon black product prepared reaches 303.15m 2 / g, median particle size (D 50 ) is only 4.02μm( Figure 3 As shown), SiO2 content reaches 98.5%, and the product quality meets the requirements of HG / T3061-2020 industry standard.
[0042] Comparative Example 1
[0043] For comparison, the difference between this comparative example and Example 1 is that when implementing step (2) for preparation and modification, the added electrolyte is a single sodium carbonate, and its amount is 6% of the mass of the clay vanadium ore vanadium acid leaching tailings, and the remaining steps are exactly the same as Example 1.
[0044] In this comparative example, the leaching rate of silicon dioxide is also as high as 98.64%, and the tailings of vanadium extraction from clay vanadium ore are also reduced by nearly 90%; however, due to the addition of a single electrolyte sodium carbonate, even when the dosage is as high as 6%, the specific surface area of the prepared modified white carbon black product is only 255.99m 2 / g, median particle size (D 50 ) is 7.60μm( Figure 4 As shown in the figure, the SiO2 content is only 96.1%. At this time, the specific surface area, particle size index and uniformity of the obtained white carbon black product have decreased to varying degrees. It can be seen that when a single electrolyte is used, the agglomeration of SiO2 colloid particles cannot achieve the ideal effect, and the dispersion cannot be more effectively improved under the premise of a smaller particle size, thereby reducing the performance parameters of the product, and the high-quality white carbon black product when the self-prepared composite electrolyte SC-1 is added is not obtained.
[0045] Comparative Example 2
[0046] For comparison, the difference between this comparative example and Example 2 is that when implementing step (2) of preparation and modification, the added electrolyte is a single sodium sulfate, and its amount is 5% of the mass of the clay vanadium ore vanadium acid leaching tailings, and the remaining steps are exactly the same as Example 2.
[0047] In this comparative example, the leaching rate of silicon dioxide is also as high as 97.2%, and the tailings of vanadium extraction from clay vanadium ore are also effectively reduced by 87.7%; however, due to the addition of a single electrolyte sodium sulfate, even when the dosage is 5%, the specific surface area of the prepared modified white carbon black product is only 269.53m 2 / g, median particle size (D 50 ) is 6.94μm( Figure 5 As shown in the figure, the SiO2 content is only 95.8%. At this time, the specific surface area, particle size index and uniformity of the obtained white carbon black product also decrease to varying degrees; it can be seen that the self-compounded electrolyte is not used, and only a single electrolyte is used. The positive synergistic effect between different single electrolytes formed by controlling and optimizing the electrolyte types and compounding ratios is lacking. The agglomeration of SiO2 colloid particles cannot achieve the ideal effect, and the dispersibility cannot be improved more effectively under the premise of a smaller particle size. The particle size of the SiO2 particles formed by agglomeration is relatively large, and the porous structure is insufficient, thereby reducing the performance parameters of the product, and the high-quality white carbon black product when the self-compounded electrolyte is added is not obtained.
[0048] Comparative Example 3
[0049] For comparison, the difference between this comparative example and Example 1 is that when implementing step (2) for preparation and modification, the added modifier is a single hexadecyltrimethylammonium bromide (CATB), and its amount is 5% of the mass of the clay vanadium ore vanadium acid leaching tailings, and the remaining steps are exactly the same as Example 1.
[0050] In this comparative example, the silica leaching rate is also as high as 98.64%, and the tailings from the vanadium extraction of clay vanadium ore are also reduced by nearly 90%; however, due to the addition of a single modifier, cetyltrimethylammonium bromide (CATB), even when the dosage is as high as 5%, the specific surface area of the prepared modified white carbon black product is only 284.37 m 2 / g, median particle size (D 50 ) is 5.35μm( Figure 6 As shown in the figure, the SiO2 content is only 96.3%. At this time, the specific surface area, particle size index and uniformity of the obtained white carbon black product all decrease within a certain range. It can be seen that although a single modifier can realize the in-situ grafting modification of the surface hydroxyl groups of the unmodified white carbon black product, adsorb the hydroxyl groups on the surface of the white carbon black, change its surface properties, and is beneficial to the formation of pores and network structures of the white carbon black, even in the case of a high dosage, the degree of modification is still not ideal. This is because the single modifier has limited coverage of the hydroxyl groups on the surface of the white carbon black particles, resulting in a decrease in the quality of the white carbon black product.
[0051] Comparative Example 4
[0052] For comparison, the difference between this comparative example and Example 2 is that when implementing step (2) of preparation and modification, the added modifier is a single sodium dodecyl sulfate (SDS), and its amount is 4% of the mass of the clay vanadium ore vanadium acid leaching tailings, and the remaining steps are exactly the same as Example 2.
[0053] In this comparative example, the silica leaching rate is also as high as 97.2%, and the tailings from the vanadium extraction of clay vanadium ore are also effectively reduced by 87.7%; however, due to the addition of a single modifier, sodium dodecyl sulfate (SDS), even when the dosage is 4%, the specific surface area of the prepared modified white carbon black product is only 271.21 m 2 / g, median particle size (D 50 ) is 6.27μm( Figure 7 As shown in the figure, the SiO2 content is only 96.5%. At this time, the specific surface area, particle size index and uniformity of the obtained white carbon black product all decrease within a certain range, which is the same as the comparative example 3 using only a single hexadecyltrimethylammonium bromide (CATB) as a modifier; it can be seen that, similarly, although a single modifier can achieve in-situ grafting modification of the surface hydroxyl groups of the unmodified white carbon black product and improve the performance of the obtained white carbon black product, even in the case of a high dosage, the degree of modification is still not ideal. This is because the single modifier has limited coverage of the hydroxyl groups on the surface of the white carbon black particles, and fails to achieve the positive synergistic effect between the two modifiers like the new combination modifier, and the degree of in-situ grafting modification of the hydroxyl groups on the surface of the white carbon black is insufficient, resulting in a decrease in the quality of the white carbon black product.
Claims
1. A process for preparing modified white carbon black from vanadium extraction acid leaching tailings from clay vanadium ore, characterized in that: The specific steps include: (1) Alkali leaching of silicon without grinding: The tailings of vanadium acid leaching from clay vanadium ore are mixed with sodium hydroxide and water in a certain ratio without grinding, and then heated for leaching reaction; after the reaction is completed, the mixture is cooled, and a filter residue and a filtrate are obtained by solid-liquid separation, and the obtained filtrate is water glass; (2) Preparation and modification: Add the self-compounded electrolyte SC-1 to water glass, and add a new combination modifier for in-situ grafting modification, then add acid for neutralization, and age at a constant temperature to produce silica gel precipitation. The silica gel is dried and ground to obtain the modified silica product; The self-compounded electrolyte SC-1 includes 60% to 80% by mass of sodium sulfate and 20% to 40% by mass of sodium carbonate; The novel combined modifier comprises components with a mass distribution ratio of 40% to 80% of hexadecyltrimethylammonium bromide and 20% to 60% of sodium dodecyl sulfate.
2. The process for preparing modified white carbon black from acid leaching tailings of clay vanadium ore according to claim 1, characterized in that: The tailings in step (1) come from the acid leaching process of vanadium extraction from clay vanadium ore, and have a silicon dioxide content of more than 85% and a particle size of -2mm to -4mm. No acid leaching and impurity removal treatment or grinding treatment is performed before alkali leaching of silicon.
3. The process for preparing modified white carbon black from acid leaching tailings of clay vanadium ore according to claim 1, characterized in that: In step (1), the alkali-slag ratio, i.e., the mass ratio of sodium hydroxide to the tailings from vanadium acid leaching of clay vanadium ore, is 0.3-1; the liquid-solid ratio, i.e., the mass ratio of water to the tailings from vanadium acid leaching of clay vanadium ore, is 3-6; the heating temperature is 180-220° C.; the reaction time is 50-100 min; and air cooling is adopted to cool the mixture to below 50° C.
4. The process for preparing modified white carbon black from acid leaching tailings of clay vanadium ore according to claim 1, characterized in that: The amount of the self-prepared electrolyte SC-1 added in step (2) is 2% to 6% of the mass of the tailings from the vanadium acid leaching of clay vanadium ore.
5. The process for preparing modified white carbon black from acid leaching tailings of clay vanadium ore according to claim 1, characterized in that: The amount of the self-assembled and compounded new combination modifier added in step (2) is 2% to 5% of the mass of the tailings from the vanadium acid leaching of clay vanadium ore.
6. The method for preparing modified white carbon black by acid leaching vanadium tailings from clay vanadium ore according to claim 1, characterized in that: In step (2), acid is added to neutralize the solution until the pH value is 7.0 to 8.5; the constant temperature aging conditions are controlled to be: 60 to 90° C., 60 to 120 min.
Citation Information
Patent Citations
Clean production technique for producing water glass and coproducing white carbon black
CN106276935A
Method for extracting white carbon black from shale vanadium extraction tailing residue
CN110467186A
Combined preparation method of nano calcium carbonate and pseudo-boehmite or white carbon black
CN112707428A
Preparation method of modified nano white carbon black
CN113912071A
Hollow silica particle, manufacturing method thereof, and hollow silica dispersion
JP2024035822A
